2022
DOI: 10.1039/d2cp01612e
|View full text |Cite
|
Sign up to set email alerts
|

Photostability of the deprotonated forms of the UV filters homosalate and octyl salicylate: molecular dissociation versus electron detachment following UV excitation

Abstract: Laser photodissociation of deprotonated salicylates reveals that electron detachment outcompetes molecular dissociation following photoexcitation due to the locations of the minimum energy crossing points on the excited state surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…OMC is primarily used as a UVB absorber in sunscreen formulations [10] with λmax = 310 nm, so it is notable that the strong band I absorption feature appears significantly red-shifted for the protonated gas-phase species. A similar red shift was observed for protonated oxybenzone [27], where protonation was found to occur in the aromatic conjugated carbonyl group, as is also expected for OMCH + . A recent extensive study by Bardeen and co-workers on UV excitation of OMC found that aggregation was important in its photochemical behaviour, with OMC aggregation leading to a complex mixture of photoproducts (truxillic and truxinic dimers), including the production of UVA photoproducts, which generated singlet oxygen [22].…”
Section: Gas-phase Absorption Spectrum Of Protonated Omcsupporting
confidence: 78%
See 2 more Smart Citations
“…OMC is primarily used as a UVB absorber in sunscreen formulations [10] with λmax = 310 nm, so it is notable that the strong band I absorption feature appears significantly red-shifted for the protonated gas-phase species. A similar red shift was observed for protonated oxybenzone [27], where protonation was found to occur in the aromatic conjugated carbonyl group, as is also expected for OMCH + . A recent extensive study by Bardeen and co-workers on UV excitation of OMC found that aggregation was important in its photochemical behaviour, with OMC aggregation leading to a complex mixture of photoproducts (truxillic and truxinic dimers), including the production of UVA photoproducts, which generated singlet oxygen [22].…”
Section: Gas-phase Absorption Spectrum Of Protonated Omcsupporting
confidence: 78%
“…OMC is primarily used as a UVB absorber in sunscreen formulations [10] with λ max = 310 nm, so it is notable that the strong band I absorption feature appears significantly red-shifted for the protonated gas-phase species. A similar red shift was observed for protonated oxybenzone [27], where protonation was found to occur in the aromatic conjugated carbonyl group, as is also expected for OMC•H + .…”
Section: Gas-phase Absorption Spectrum Of Protonated Omcsupporting
confidence: 77%
See 1 more Smart Citation
“…It is not always only spectroscopy and theory that are used to study MAs. In Caroline Dessent's lab, 22 photo dissociation and mass spectrometry were used to study the competition between fragmentation and electron detachment involving MAs consisting of the deprotonated forms of two molecules used in sunscreens. Such an approach was important in determining how long these molecules could protect against UV radiation before being photodegraded.…”
Section: A Conventional (Valence)mentioning
confidence: 99%
“…[13][14][15][16] It is particularly useful in the context of analysing photoproducts, since these can be straightforwardly identified by mass spectrometry following photoexcitation and decay of a precursor ion. In these experiments, the organic chromophore is introduced to the MS via electrospray ionization and studied either as the protonated or deprotonated form of the molecule, [17][18][19] or in a complex with an attached ion-tag, such as an alkali metal cation. [16] The ionic sunscreen precursor ion is isolated in an ion trap, where it is irradiated with photons across the UV range, and the photoproducts obtained at each photoexcitation energy measured.…”
Section: Introductionmentioning
confidence: 99%